Salmonella enterica in the Chicken: How it has Helped Our Understanding of Immunology in a Non-Biomedical Model Species - Wigley, Paul (Frontiers in Immunology, 2014)
Salmonella infection of the chicken is important both as a source of foodborne human salmonellosis and as a source of disease in the chicken itself. Vaccination and other control strategies require an understanding of the immune response and as such have been important in understanding both mucosal immunity and more generally the response to bacterial infection. In this review we discuss the contribution the study of avian salmonellosis has made to understanding: Innate immunity including the function of phagocytic cells, pattern recognition receptors and defensins. The mucosal response to Salmonella infection and its regulation and the contribution this makes in protection against infection and persistence within the gut and future directions in better understanding the role of TH17 and Tregs in this response. Finally we discuss the role of the immune system and its modulation in persistent infection and infection of the reproductive tract. We also outline key areas of research required to fully understand the interaction between the chicken immune system and Salmonella and how infection is maintained in the absence of substantive gastrointestinal disease.